2021
DOI: 10.3390/dairy2040041
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Membrane Filtration to Increase Native Whey Proteins in Infant Formula

Abstract: The introduction of membrane filtration during infant milk formula (IMF) processing represents an innovative approach to increasing native protein content compared to standard IMF. The objective of this study was to compare IMF powder produced using a standard process and IMF produced from raw bovine skim milk with added whey protein isolate using a split-stream process incorporating a ceramic 1.4 μm filter followed by a polyvinylidene difluoride polymeric 0.2 μm filter. Retentates from 0.2 μm microfiltration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…4) have been reported previously and described in detail. 22 The results from both SDS-PAGE and SEC-HPLC showed that the amounts of water soluble whey proteins were continuously declining during the course of digestion, while the peptide release reached a peak at GE4 in the MEM-IMF samples. Interestingly, the amount of water soluble proteins detected in the HT-IMF digesta was similar from GE3 to GE5 (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…4) have been reported previously and described in detail. 22 The results from both SDS-PAGE and SEC-HPLC showed that the amounts of water soluble whey proteins were continuously declining during the course of digestion, while the peptide release reached a peak at GE4 in the MEM-IMF samples. Interestingly, the amount of water soluble proteins detected in the HT-IMF digesta was similar from GE3 to GE5 (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…5B2–B5). 22 Moreover, our previous study had demonstrated that MEM-IMF exhibited residual activity of indigenous enzymes, such as alkaline phosphatase, whereas these enzymes are fully inactivated in the HT-IMF. 22 Hence, MEM-IMF shows a higher initial primary amine content (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations